الدور الوسيط للإبداع الإداري بين نُظم المعلومات الإدارية وأداء مديري مدارس محافظة الداخلية بسلطنة عُمان - أحمد بن عبد الله بن مسعود العزيزي; ‘Ahmad ibn Abdullah ibn Mas’ud Al-'Azizi (Universiti Sains Islam Malaysia, 2024)
Matric:4171042 (FPBU)